Trends and traps in the reconstruction of early herding societies in southern Africa - Fauvelle-Aymar, F.-X.; Sadr, K. (Southern African Humanities, 2021)
Introducing the Khoekhoen volume. To cite this article: Fauvelle-Aymar, F.-X. & Sadr, K. 2008. Trends and traps in the reconstruction of early herding societies in southern Africa. Southern African Humanities 20: 1-6.